DELEGATION OF PARTIAL AUTHORITY OF MATARAM MAYOR TO SUB-DISTRICT AND VILLAGE HEADS REGULATED BY REGULATION NUMBER 22 OF 2013 - Bq. Baktiyanti (Jurnal IUS Kajian Hukum dan Keadilan, 2014)
Partial Delegation Of Authority Mataram Mayor To Sub-District And Village Heads Regulated By Mataram Mayor Regulation Number 22 Year 2013 About Partial Delegation Of Authority Mayor To Sub-District And Village Heads. Delegation of authority among levels of government or organizational structure is common in the administration of government affairs period of regional autonomy. Mataram’s mayor Regulation No. 22 Year 2013 About Partial Delegation Of Authority Mayor To Sub-District And Village Heads, is one of the local laws governing the delegation of authority in Mataram. The problem in this study consists of First , the correspondence between the Mayor Mataram Regulation No. 22 Year 2013 on legislation higher ; Second, Mayor Mataram Implementation Regulation No. 22 of 2013 ;Third, efforts to overcome obstacles in the implementation of the regulations mayor. This study used a Normative and Empirical approach, the data obtained in the form of primary and secondary data in the form of legal materials. The data collection techniques performed by the study documentation and interviews. Then the obtained data were analyzed qualitatively. The results showed that the Mayor Mataram Regulation No. 22 of 2013 as the legal basis delegation of authority to the sub-district and village heads in the city of Mataram, was contrary to the Regional Regulation No. 5 of 2008 Mataram. This raises a legal uncertainty and lead to overlapping of authority between agencies associated with the delegation of authority. Besides the fact that it met affairs delegated to the sub-district and urban village mayor in Mataram , mostly a long and routine affairs that has been carried out by sub-district and village heads in Mataram. The new affairs mentioned is House Rental management, implementation of environmental cleanliness Management, and restructuring street vendors (PKL). Regarding the constraints encountered in the implementation of the delegation include budgetary constraints, facility / infrastructure support and the absence of additional personnel and community participation to support the execution of these tasks is low .Keyword : Delegation of authority of, Mayors and Village Chief